Pendidikan Karakter Holistik: Menyatukan Kecerdasan Intelektual dan Emosional dalam Perkembangan Diri - Al Zari, Rifki Dwi; Asbari, Masduki; Yudhistira, Aji (Journal of Information Systems and Management (JISMA), 2025)
This study aims to understand how intelligence and ego interact in the process of character formation and self-development, using Dr. Tirta's personal experience as the main case study. Using a descriptive qualitative method, this study relies on observation and note-taking techniques from in-depth dialogues between Gita Wirjawan and Dr. Tirta in the video “For Dr. Tirta, Intelligence is Never Enough,” which highlights the dynamics of academic pressure, family demands, and a reflective journey in balancing intelligence and humility. The results of the study show that intellectual intelligence without ego control can lead to rigidity in thinking, difficulty accepting criticism, and stagnation in emotional development. However, Dr. Tirta's experience also shows that through the support of family, teachers, a culture of reading, and a continuous process of self-reflection, individuals can develop a mature, adaptive character and be able to manage their ego constructively. Thus, this study emphasizes the importance of integrated character education, which not only emphasizes academic achievement but also the development of emotional and moral intelligence.